Measurement of the photon identification efficiencies with the ATLAS detector using LHC Run-1 data - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2016)
The algorithms used by the ATLAS Collaboration to reconstruct and identify prompt photons are described. Measurements of the photon identification efficiencies are reported, using 4.9 fb[Formula: see text] of pp collision data collected at the LHC at [Formula: see text] [Formula: see text] and 20.3 fb[Formula: see text] at [Formula: see text] [Formula: see text]. The efficiencies are measured separately for converted and unconverted photons, in four different pseudorapidity regions, for transverse momenta between 10 [Formula: see text] and 1.5 [Formula: see text]. The results from the combination of three data-driven techniques are compared to the predictions from a simulation of the detector response, after correcting the electromagnetic shower momenta in the simulation for the average differences observed with respect to data. Data-to-simulation efficiency ratios used as correction factors in physics measurements are determined to account for the small residual efficiency differences. These factors are measured with uncertainties between 0.5% and 10% in 7 [Formula: see text] data and between 0.5% and 5.6% in 8 [Formula: see text] data, depending on the photon transverse momentum and pseudorapidity.